Willingness to receive mpox vaccine among men who have sex with men: a systematic review and meta-analysis - Jiajia Liu; Siying Liu; Simin Yu; Xiaoyu Du; Jiaqi Hao; Ruixue Hui; Amos Buh; Wenjun Chen; Jia Chen (BMC Public Health, 2024)
Abstract Background Since May 2022, mpox outbreaks have been occurring in non-mpox endemic areas, with the main population affected being men who have sex with men (MSM). Outbreak prevention and control depend not only on the effectiveness of vaccines but also on people’s willingness to receive these vaccines. Currently, there is lack of synthesis on the overall rates and influence factors of MSMs’ willingness to vaccinate against mpox. Therefore, we systematically reviewed studies that assessed the willingness of MSM to receive mpox vaccine. Methods Studies reporting mpox vaccination intentions among MSM were included by searching five databases (PubMed, Web of Science, EMBASE, CINAHL, and SCOPUS) from inception to May 12, 2024. The quality of the included literature was assessed using Joanna Briggs Institute’s critical appraisal tool. The data analysis software is Stata17. The systematic review has been registered with Prospero (registration ID: CRD42023452357). Results Twenty cross-sectional studies were included in the review. Meta-analysis results showed that the pooled willingness rate of vaccinate against mpox was 77.0% (95% CI: 73-81%, I2 = 99.4%). According to subgroup analysis, study countries (P = 0.002), research sample size (P = 0.001), and whether participants were infected with HIV (P = 0.002) may be sources of heterogeneity. The results of the meta-analysis of influencing factors showed that more number of sexual partners (OR: 2.24, 95%CI: 1.86–2.69), pre-exposure prophylaxis use (OR: 6.04, 95%CI: 4.80–7.61), history of sexually transmitted infections (OR: 2.96, 95%CI: 2.33–3.76), confidence in the vaccine’s effectiveness (OR: 2.79, 95%CI: 2.04–3.80) and safety (OR: 10.89, 95%CI: 5.22–22.72), fear of mpox infection (OR: 2.47, 95%CI: 2.11–2.89) and epidemics (OR: 2.87, 95%CI: 2.22–3.70), high mpox knowledge (OR: 2.35, 95%CI: 1.51–3.66), and the belief that people at high risk should be prioritized for vaccination (OR: 3.09, 95%CI: 1.40–6.84) were the facilitators of vaccine willingness. In addition, as a secondary outcome, meta-analysis results showed a pooled unwillingness rate of 16% (95% CI: 13-20%, I2 = 98.1%, 9 studies). Conclusion Willingness to vaccinate mpox was high among MSM, but some participants still had negative attitudes towards vaccination. Therefore, the Ministry of Public Health should develop targeted and effective strategies against those influencing factors to prevent and manage mpox outbreaks.